A Content Analysis of Al-Kitab Al-Asasi the Lens of Rushdi Ahmad Thu’aimah’s Theories - Sanah, Siti; Bustomi, Jenal; Azhar, Ruly Syaepul; Saad Bahaaeldin, Mohamed (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This study aims to analyze the content of Al-Kitab Al-Asasī fi Ta'līm Al-Lughah Al-Arabiyyah Li Ghair Al-Nāthiqīna Bihā to evaluate its alignment with Rusydi Ahmad Thu'aimah's theoretical standards for Arabic textbooks. The analysis focuses on presentation, language, culture, exercises, and supplementary materials. This study uses a qualitative approach, content analysis, and library research with documentation techniques for data collection. The findings reveal that the book aligns with Thu'aimah's criteria, demonstrating strengths in presentation, linguistic accuracy, cultural relevance, and exercise quality, making it suitable for teaching Arabic to non-native speakers. This research highlights the importance of adhering to established standards in textbook development to create effective learning materials. The implications suggest that educators and curriculum developers should prioritize compatibility with theoretical frameworks to enhance language instruction. Future studies could expand this analysis to compare multiple Arabic textbooks, explore the effectiveness of these standards in classroom settings, and assess how digital adaptations of textbooks can complement traditional methods. Additionally, integrating student feedback into textbook evaluation could provide deeper insights into user-centered design in language education.